The impact of the COVID-19 pandemic on job productivity among housekeeping employees in Southeast Malaysia / Siti Nor Fadillah Ahmad Shariff … [et al.] - Ahmad Shariff, Siti Nor Fadillah; Sulong, Siti Nurhanifah; Omar, Massyittah; Jaafar, Zuratulraha (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Housekeeping personnel often experience heavy workloads, long workweeks, and low pay, which can negatively impact their productivity and increase their stress levels. However, the hotel industry in Malaysia has received less attention in terms of research compared to the banking and healthcare sectors. Therefore, this study employs the Effort Reward Imbalance (ERI) hypothesis to investigate the relationship between housekeeping personnel's job stress and productivity during the COVID-19 pandemic. Data was collected from 210 housekeeping staff members at 11 hotels in Desaru, Johor, using basic random sampling methods. The findings indicate a significant negative correlation between workload, long working hours, and low pay. Nonetheless, among cleaning staff members in the hotels in Desaru, Johor there is a substantial association between workload and job performance, which may impair their productivity.